A new look at the employment and recidivism relationship through the lens of a criminal background check - Denver, Megan (Criminology, 2017)
Criminal background checks are increasingly being incorporated into hiring decisions by employers. Although originally uncompromising—almost anyone with a criminal record could be denied employment—court rulings and policy changes have forced criminal background checks to become more nuanced. One motivation for allowing more individuals with criminal records to work is to decrease recidivism and encourage desistance. In this article, we estimate the causal impact of receiving a clearance to work on subsequent arrests for individuals with criminal records who have been provisionally hired to work in certain nonlicensed health-care jobs in New York State (N = 6,648). We employ an instrumental variable approach based on a substantive understanding of the state-mandated criminal background check process. We examine age-graded effects within this group of motivated individuals and differential effects by sex in the rapidly growing health-care industry, which is typically dominated by women. Our estimated local average treatment effect indicates a 2.2-percentage-point decrease in the likelihood of a subsequent arrest in 1 year and a 4.2-percentage-point decrease over 3 years. We find meaningful variations by sex; men are 8.4 percentage points less likely to be arrested over the 3-year period when cleared compared with a 2.4-percentage-point (and nonsignificant) effect for women. Older women in particular are driving the nonsignificant results for women.